Ukrainian Studies in the Publications of Vasyl Stefanyk Precarpathian National University - Bihusiak, Mykhailo; Hutsuliak, Oleh (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The review covers the major researches by the scholars of Vasyl Stefanyk Precarpathian National University in the fields of Ukrainian history, philology, psychology, philosophy and religious studies, political science, pedagogy – a range of topics under the umbrella title of ‘Ukraine and the World’. The activity of the University’s leading scholars and schools of Ukrainian studies is highlighted